ICT Competency Analysis of Pre-Service Science Teacher in the Teaching Kit Using Web-Based E-Portfolios Blog on Science Instruction in English Courses - Urwatin Wusqo, Indah; Khusniati, Miranita; Dwita Hardianti, Risa (International Journal of Engineering and Technology, 2018)
An analysis of different frameworks for 21st-century learning show consensus about the skills that are needed for living and working in the 21st century. ICT competency is one of the 21st skills that are considered essential as the same as with collaboration, communication, citizenship, problem-solving, critical thinking, creativity, and productivity. The study aims to analyses and explores the ICT competency from pre-service science teacher through the teaching kit using the web-based e-portfolios blog on Science Instruction in English courses. The standard ICT competence measurement was conducted through a survey. The novelty of this study is that the ICT capability measurement in this study was done through the analysis of products produced by students. The products are portfolio on the web blog. The subject of research is the sixth-semester students who receive Science instruction in English course. Research type is descriptive qualitative. The results showed the value: Regarding ICT in e-Teaching Kit Using Web-Based E-Portfolios Blog competency, 20% of PST Teachers are at very high level, 75% are at high level and 5% are at sufficient level. The indicators in ICT competency that pass the knowledge creation are productivity tools, authoring tools, administration, and communication & collaboration. But no one passes knowledge creation indicators they are the internet and educational software.Â